تطبيق أساليب التعلم بالمحاكاة في تدريس مقرر الجغرافيا بمؤسسات التعليم الأساسي والثانوي مصراتة (Journal of Academic Research, 2024)
The study aims to investigate the possibility of applying simulation learning method in Geography subject which is taught at primary and secondary schools in Misurata during the academic year 2023-2024. The study adopted a field study method to explore how simulation methods are used in actual practice. Schools that have laboratories for Geography subject were calculated and the total number was 18 schools. This number represented 8.9% of the total number of schools located within the investigated area, which has 202 schools. After statistical analysis of questionnaire data was done, the study reached a set of results and recommendations.  One of these results was that use of the simulation learning method in Geography subject at both primary and secondary schools was not as effective as it could be.  However, the results showed a real desire among teachers who held the position of laboratory supervisors, to apply the simulation methods because of their benefits in education. The study also suggested some recommendations including necessity of using the simulation learning method in the field of education and learning, development of curricula and employment of  multimedia. Furthermore, the study recommended conduction of training courses that prepare Geography teachers to use computers and various software types, to provide an opportunity for each teacher to deal with educational programs. Another recommendation was to give more focus on simulation programs, expand their utilization in various specializations and support them financially and support their use.